Survey on roselle juice (Hibiscus sabdariffa L) preparation in the West Region of Cameroon: An evaluation of the effect of different formulations of this juice on some biological properties in rats - Ghislain Maffo Tazoho (Journal of Agriculture and Food Research, 2022)
Continuous efforts in the search for rich food crops or diets are ongoing, and in order to contribute to this effect, this study was designed to identify the processing methods and to evaluate the effect of consuming roselle juice prepared with three plant extracts (pineapple peelings, lemongrass leaves, avocado leaves) and synthetic flavour on some nutritional and biochemical properties in rats.The processing methods of roselle juice were identified via a questionnaire administered to some roselle juice makers and the biological properties of the juice were assessed with conventional methods.The results obtained show that the preferred extraction methods of roselle juice by the population is hot extraction and that 4.55; 9.09; 4.55; 18.18 and 40.91% of people used respectively pineapple peelings, lemongrass leaves, avocado leaves, synthetic flavouring agents and a mixture of these different flavour sources during the preparation of the juice. The effect of consumption of roselle juice prepared by adding plant extracts and synthetic flavour showed that the calyces-pineapple peelings juice had the highest acceptability in terms of volume consumed (15.24 ± 0.61 mL/day). The roselle juice flavoured with the pineapple peelings, lemongrass and synthetic flavour demonstrated no positive effect on blood parameters in rats. However, the avocado leaves-calyces juice increased the red blood cells, haematocrit and haemoglobin levels in the rats. The decrease of transaminases in all groups of rats compared to the control group was also observed.These findings show that the pineapple peelings-roselle juice should be valorized because of its important organoleptic characteristics. Also, the avocado leaves-roselle juice should be valorized since its consumption showed some positive effects on haematological parameters. Roselle juice flavoured or not could be hepatoprotective.